Cluster Analysis for Extension and Other Behavior Change Practitioners: Introduction - Laura A. Sanagorski Warner (EDIS)
Helping people adopt behaviors to improve social, economic, and environmental conditions is central to Extension’s mission. This new publication describes cluster analysis, a quantitative technique that can be used to identify audience subgroups so that tailored education and communications can be designed, and conveys its value in supporting behavior change to help readers understand how this technique is applied and encourage others to consider using it. Written by Laura A. Warner; 5 pp. https://edis.ifas.ufl.edu/wc399